ANALISIS KOMUNIKASI ANTARBUDAYA DALAM KELUARGA PERKAWINAN CAMPURAN ANTARA SUKU BATAK DAN SUKU MINANG DI PEKANBARU - Imadah Thoyyibah (Ensiklopedia of Journal, 2023)
This study was made with the aim of seeing how intercultural communication occurs in mixed-marriage families between the Minang and Batak tribes, which have differences in their family system, where the Minang tribe adheres to the matrilineal system while the Batak tribe adheres to the patrilineal system. This research uses a qualitative descriptive method that focuses on field findings based on observations, interviews, and documentation. The subject or informant was taken from three mixed marriage couples in Pematang Kapau sub-district, Tenayan Raya district. The results of the study showed that intercultural communication in mixed marriage families tends to cause assimilation rather than acculturation, that is, it tends to give rise to a new habit in the family. The process of meaning in intercultural communication involves three aspects; sensations, perceptions, and states of consciousness. These three aspects are very helpful for mixed marriage couples in communicating and understanding the differences in cultural backgrounds in the family.Keywords: Intercultural Communication, Mixed-Marriage, Culture, Assimilation, Acculturation.